The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1037/0033-295x.106.1.210
|View full text |Cite
|
Sign up to set email alerts
|

A note on superadditive probability judgment.

Abstract: Recent studies have demonstrated subadditivity of human probability judgment: The judged probabilities for an event partition sum to more than 1. We report conditions under which people's probability judgments are superadditive instead: The component judgments for a partition sum to less than 1. Both directions of deviation from additivity are interpreted in a common framework, in which probability judgments are often mediated by judgments of evidence. The 2 kinds of nonadditivity result from differences in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(51 citation statements)
references
References 9 publications
3
46
2
Order By: Relevance
“…Other researchers (e.g., Ayton, 1997) have reported that people's probability judgments tend to be subadditive (i.e., the sum of the individualestimates is greater than one). And evidence of superadditivityin the case of binary complementarity also has been found (see, e.g., Macchi, Osherson, & Krantz, 1999).…”
Section: The Additivity Principlementioning
confidence: 92%
“…Other researchers (e.g., Ayton, 1997) have reported that people's probability judgments tend to be subadditive (i.e., the sum of the individualestimates is greater than one). And evidence of superadditivityin the case of binary complementarity also has been found (see, e.g., Macchi, Osherson, & Krantz, 1999).…”
Section: The Additivity Principlementioning
confidence: 92%
“…However, some descriptive models of judgment predict that judgments should be either additive or superadditive (e.g., Shafer, 1976), while others predict that they should be either additive or subadditive (e.g., Tversky & Koehler, 1994). Much of the literature in this area supports the latter prediction (e.g., Fischhoff et al, 1978;Fox, Rogers, & Tversky, 1996;Rottenstreich & Tversky, 1997;Tversky & Fox, 1995); other research, however, supports the former (e.g., Macchi, Osherson, & Krantz, 1999). Tversky and Koehler (1994) developed support theory (ST) to accommodate the finding that different descriptions of the same event lead to different subjective judgments for the event.…”
mentioning
confidence: 86%
“…Moreover, partition elements sometimes attract a dearth of support rather than a surplus, leading to superadditivity. For example, in Macchi et al (1999), one group of undergraduates (in Italy) gave their probability that the Duomo in Milan is taller than Notre Dame in Paris, whereas another group gave the probability that Notre Dame is taller than the Duomo. All participants were informed that the heights are different.…”
Section: Introductionmentioning
confidence: 99%